More on set-magic graphs - Thomas, Ullas (International Journal of Advanced Mathematical Sciences, 2015)
This paper contains certain properties of set-magic graphs and obtained the set-magic number of certain classes of graphs. All spanning super graphs of a set-magic graph always set-magic and all cycles and Hamiltonian graphs are set-magic. Also set-magic number of any cycle of size 2n is always greater than n.